Designing a flexible and low–cost testbed for Wireless Sensor Networks. (24th February 2012) - Guo, Cheng; Prasad, R. Venkatesha; He, Jiang Jie; Jacobsson, Martin; Niemegeers, Ignas G.M.M.
Setting up a Wireless Sensor Network (WSN) for an experiment is both time consuming and effort intensive. Many testbeds connect and manage experimental nodes using wires and gateways. It leads to extra cost, extensive setup and maintenance effort and dedicated deployment place. We propose a framework for implementing a flexible and low–cost wireless for sensor network testbed (FIST). FIST consists of only experimental nodes. Both testbed and experiment management are carried out by the nodes wirelessly without extra devices. Thus, the testbed can be easily and quickly deployed anywhere. We present our framework and also a case study using FIST.